Patients' prognosis of intrahepatic cholangiocarcinoma and combined hepatocellular‐cholangiocarcinoma after resection. (13th August 2019) - Song, Peipei; Midorikawa, Yutaka; Nakayama, Hisashi; Higaki, Tokio; Moriguchi, Masamichi; Aramaki, Osamu; Yamazaki, Shintaro; Aoki, Masaru; Teramoto, Kenichi; Takayama, Tadatoshi
Abstract: Combined hepatocellular‐cholangiocarcinoma (cHCC‐CC) and intrahepatic cholangiocarcinoma (ICC) are classified into one category, but comparison of prognosis of the two carcinomas remains controversial. The aim of the current study was to investigate surgical outcomes for patients with ICC or cHCC‐CC who underwent resection in order to elucidate whether the classification of ICC and cHCC‐CC is justified. Subjects were 61 patients with ICC and 29 patients with cHCC‐CC who underwent liver resection from 2001 to 2017. Clinic‐pathological data from the two groups were compared. Tumor number and vascular invasion were independent risk factors for recurrence‐free survival (RFS) in both groups ( P  < .001 for both). Of note, for patients with ICC, tumor cut‐off size of 5 cm showed statistical significance in median RFS (>5 cm vs ≤5 cm, 0.5 years vs 4.0 years, P  = .003). For patients with cHCC‐CC, tumor cut‐off size of 2 cm showed statistical significance in median RFS (>2 cm vs ≤2 cm, 0.6 years vs 2.6 years, P  = .038). The median RFS of patients with cHCC‐CC was 0.9 years (95% confidence interval: 0.3‐1.6), which was poorer than that of patients with ICC (1.3 years, 0.5‐2.1) ( P  = .028); the rate of RFS at 5 years was 0% and 37.7% respectively. Our study supports the concept of classifying ICC and cHCC‐CC into different categories because of a significant difference in RFS between the two. Abstract : Our study supports the concept of classifying ICC and cHCC‐CC into different categories because of a significant difference in RFS between the two.